MassARRAY: a high-throughput solution for rapid detection of foodborne pathogens in real-world settings - Suebwongsa, Namfon; Jiemsup, Surasak; Santiyanont, Pannita; Hirunpatrawong, Piyapha; Aswapairin, Pornsiri; Thongkum, Monthathip; Panumars, Prakaymars; Chokesajjawatee, Nipa; Wongsrichai, Supaporn; Koompa, Pichet; Yongkiettrakul, Suganya (Frontiers in Microbiology, 2024)
Introduction: Bacterial foodborne pathogens pose a substantial global public health concern, prompting government agencies and public health organizations to establish food safety guidelines and regulations aimed at mitigating the risk of foodborne illness. The advent of DNA-based amplification coupled with mass spectrometry, known as MassARRAY analysis, has proven to be a highly precise, sensitive, high-throughput, and cost-effective method for bacterial detection. This study aimed to develop, validate, and evaluate a MassARRAY-based assay for the detection and identification of significant enteropathogenic bacteria. Methods: The MassARRAY-based assay was developed for the detection of 10 crucial bacterial foodborne pathogens, including Campylobacter coli, Campylobacter jejuni, Clostridium perfringens, Escherichia coli/ Shigella spp., Enterococcus faecalis, Enterococcus faecium, Listeria monocytogenes, Salmonella spp., and Staphylococcus aureus. The assay was optimized using the reference gDNA (n = 19), followed by validation using gDNA (n = 85) of reference and laboratory isolates. Additionally, the evaluation of the assay's reaction using a mixture of gDNA from all nine targeted species was performed. Moreover, the limit of detection of the developed MassARRAY-based assay was determined using bacterial cells. Furthermore, the validation method for field samples was evaluated by comparing it with standard microbiological testing methods routinely analyzed. Results: The developed MassARRAY-based assay demonstrated 100% concordance with known bacterial pure cultures. The assay’s reaction using a mixture of gDNA from all nine targeted species revealed the MassARRAY’s capability to detect all targeted species in a single assay with the lowest concentration of 1 ng/µL of gDNA. The limits of detection of the assay range from 357 ± 101 to 282,000 ± 79,196 cells. Moreover, the validation of the assay in field samples revealed a 100% correlation between the data obtained from the standard microbiological method and the MassARRAY-based assay. Discussion: These findings suggested that the developed MassARRAY-based assay exhibited the excellence in high-throughput detection of foodborne bacterial pathogens with high accuracy, reliability, and potential applicability within real-world field samples.